Remote Monitoring for the Management of Spasticity: Challenges, Opportunities and Proposed Technological Solution - Kavit R. Amin; Samuel R. Smith; Amit N. Pujari; Syed Ali Raza Zaidi; Robert Horne; Atif Shahzad; Christopher Walshaw; Christy Holland; Stephen Halpin; Rory J. O'Connor (IEEE Open Journal of Engineering in Medicine and Biology)
Spasticity is disabling feature of long-term neurological conditions that has substantial impact on people’ quality of life. Assessing spasticity and determining the efficacy of current treatments is limited by the measurement tools available in clinical practice. We convened an expert panel of clinicians and engineers to identify a solution to this urgent clinical need. We established that a reliable ambulatory spasticity monitoring system that collates clinically meaningful data remotely would be useful in the management of this complex condition. This paper provides an overview of current practices in managing and monitoring spasticity. Then, the paper describes how a remote monitoring system can help in managing spasticity and identifies challenges in development of such a system. Finally the paper proposes a monitoring system solution that exploits recent advancements in low-energy wearable systems comprising of printable electronics, a personal area network (PAN) to low power wide area networks (LPWAN) alongside back-end cloud infrastructure. The proposed technology will make an important contribution to patient care by allowing, for the first time, longitudinal monitoring of spasticity between clinical follow-up, and thus has life altering and cost-saving implications. This work in spasticity monitoring and management serves as an exemplar for other areas of rehabilitation.